PENGEMBANGAN MEDIA PERMAINAN LUDO “CERDAS” (CEGAH RISIKO DIABETES MELITUS ANAK SEDINI MUNGKIN) DI TK AL-IHSANIYYAH - Rifa Nur Aqiilah; Rahmat Sudiyat (Politeknik Kesehatan Kemenkes Bandung, 2024)
According to the Indonesian Medical Association (IDI), January 2023, the number of diabetes cases in children will increase 70 times. This is because the prevention of Diabetes Mellitus in early childhood is still not maximized. So that because the target is an early age child, the suitable media to use is the “CERDAS” ludo game media regarding the prevention of Diabetes Mellitus. This study used the RnD (Research and Development). The development model uses ADDIE which includes qualitative research with a total sampling technique of 14 people through in-depth interviews. Quantitative research was conducted on 1 material expert, 1 media expert and 8 small groups and 18 large groups. The results of the analysis show the need for ludo game media, Design shows that ludo games have appropriate images and material, Development of ludo games gets decent results on media experts and is very feasible on material experts and small scale, Implementation shows that ludo games are very feasible to use and Evaluation shows the target follows the activity well and media development is very feasible to use. Ludo media “CERDAS” is said to be very feasible to use in learning with a percentage of 99.36%